2013
DOI: 10.1186/1423-0127-20-29
|View full text |Cite
|
Sign up to set email alerts
|

Control of post-translational modifications in antithrombin during murine post-natal development by miR-200a

Abstract: BackgroundDevelopmental haemostatic studies may help identifying new elements involved in the control of key haemostatic proteins like antithrombin, the most relevant endogenous anticoagulant.ResultsIn this study, we showed a significant reduction of sialic acid content in neonatal antithrombin compared with adult antithrombin in mice. mRNA levels of St3gal3 and St3gal4, two sialyltransferases potentially involved in antithrombin sialylation, were 85% lower in neonates in comparison with adults. In silico anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…33 MiR-200a targeted mRNA levels of ST ST3GAL3 and ST3GAL4, which potentially involved in antithrombin sialylation. 34 Our recent results also showed that miR-224-3p directly targeted 3′-UTR of fucosyltransferase FUT4 mRNA and sensitized drug-resistant breast cancer cells to chemotherapeutics and reduced the growth rate of breast cancer xenografts in vivo . 35 …”
Section: Discussionmentioning
confidence: 74%
“…33 MiR-200a targeted mRNA levels of ST ST3GAL3 and ST3GAL4, which potentially involved in antithrombin sialylation. 34 Our recent results also showed that miR-224-3p directly targeted 3′-UTR of fucosyltransferase FUT4 mRNA and sensitized drug-resistant breast cancer cells to chemotherapeutics and reduced the growth rate of breast cancer xenografts in vivo . 35 …”
Section: Discussionmentioning
confidence: 74%
“…AT from newborn mice has an incomplete content of sialic acid, which may be explained by the lower expression of two sialyltransferases. Our data suggest that miR‐200a, an miRNA expressed in liver and inversely correlated with the expression of the two sialyltransferases, may be, in part, involved in their regulation . Thus, the role of miRNAs in hemostasis does not seem to be restricted to the direct control of proteins, but could be extended to include indirect effects on elements involved in transcriptional or post‐translational processes.…”
Section: Mirna As a Regulator Of The Hemostatic Systemmentioning
confidence: 87%
“…Indeed, miR‐18a and miR‐19b, two potential regulators of AT in the liver, as predicted by two different and widely used algorithms, were inversely correlated with SERPINC1 mRNA levels during the first 19 days of postnatal development . The regulation may be even more complex, as the qualitative changes observed in AT during development may also be regulated by miRNAs , which may have functional consequences for hemostasis. AT from newborn mice has an incomplete content of sialic acid, which may be explained by the lower expression of two sialyltransferases.…”
Section: Mirna As a Regulator Of The Hemostatic Systemmentioning
confidence: 99%
“…Vaiana et al demonstrated that MGAT4A, an N-acetylglucosamintltransferase that installed the β-1, 4 branch of N-glycans, was directly regulated by miR-424 in multiple mammary epithelial cell lines [ 31 ]. MiR-200a might target ST3GAL3 and ST3GAL4 sialyltransferases, which potentially involved in antithrombin sialylation, were 85% lower in neonates in comparison with adults [ 32 ]. MiR-199a targeted ST6GAL1 and reduced both the sialylation and the protein level of Necl-2 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%